Association of fibrinogen to albumin ratio with sepsis-associated acute kidney injury: A retrospective cohort study based on the MIMIC-IV database - Tuan Li; Muyan Diao; Feng Lu; Zhuojian Zeng; Zhiwen Chen; Shengyuan Su; Yuehui Zhang (PLoS ONE, 2026)
Purpose Sepsis-associated acute kidney injury (SA-AKI) is a critical complication associated with negative outcomes. However, the effective prevention of SA-AKI is limited. This retrospective cohort study, which used the MIMIC-IV database, investigated the association between fibrinogen-to-albumin ratio (FAR) and SA-AKI. Materials and methods The retrospective cohort study involved 1,771 sepsis patients in MIMIC-IV database. Multivariable logistic and Cox regression models were used to estimate ORs/HRs with 95% CIs for incident SA-AKI. Sensitivity analyses, including stratified analyses and RCS curve, assessed the strength of the association. The predictive performance was compared to other marker using ROC curves and AUCs. Results An elevated FAR level (≥110.74) was found to be associated with an elevated risk of SA-AKI (adjusted OR 1.55, 95%CI 1.11–2.18, P = 0.011), but the association was timing, it reached statistical significance only when SA-AKI occurred after ICU day 3 (adjusted HR 5.17, 95%CI 1.81–14.72, P = 0.002). Subgroup analyses indicated that chronic obstructive pulmonary disease (COPD) and hypertension interacted in this association. In sepsis patients without COPD and hypertension, high FAR (≥110.74) was linked to SA-AKI (adjusted OR 2.31, 95%CI 1.40–3.82, P = 0.001), with statistical significance also occurring 3 days after ICU admission (adjusted HR 8.57, 95%CI 1.88–38.94, P = 0.005). The RCS curve showed a linear relationship between FAR and SA-AKI (P for non-linearity: 0.415). ROC analyses showed that FAR combined with SOFA slightly outperformed SOFA alone (AUC 0.697 vs. 0.678, P = 0.004). Conclusions An elevated FAR level was associated with an increased incidence of SA-AKI in patients without COPD and hypertension. However, this association reached statistical significance only when SA-AKI occurred after ICU day 3. Further research is needed to investigate this association.